MENCINTAI BUMI SEBAGAI RUMAH BERSAMA SELURUH CIPTAAN BERDASARKAN PEMIKIRAN PARA BAPA GEREJA - Agus Widodo (Jurnal Orientasi Baru, 2017)
This research aims to seek inspiration and relevance of the thought of the Fathers of the Church to answer our current ecological problems. The method used is to focus on discovering the writings of Church Fathers that convey the universe in relation to God and human being. Then, some key ideas on ecology will be drawn. In conclusion, based on this research, the Fathers of the Church have a highly positive and appreciative point of view of the universe: all are well-created by God, and they are beautiful, harmonious, having intrinsic value and being a sign of Gods presence. The world is indeed a home for all creation, both human and non-human. Human beings have obligation to the universe that is to appreciate and maintain its beauty, goodness, and harmony, as well as to manage and cultivate the earth, to offer and sanctify its fruit to the Lord, and therefore to live in brotherhood with the whole creation. Humans are allowed to make use of non-human creations yet wisely: not only to satisfy worldly needs (uti), but also to achieve eternal happiness (frui). Consequently, human beings must live an ecological asceticism, by limiting the use of natural resources and aiming at improvement of the quality of life instead of on the standard of living.